Public Opinion Research Is A Factor In Maintaining Social Stability - Saitkasimov Akbar Isaxanovich; Jahongir Ismoilov (Peerian Journals Publishing, 2024)
Studying public opinion and developing strategic systems to conduct these processes systematically is a crucial task today. It is equally important to strengthen political, philosophical, psychological, and sociological research within society
Keywords: State; civil society; stability